Studies on Radiopharmaceuticals - Tanaka, Akira; Tojyo, Ken - ichi; Urakubo, Goro; Miki, Makoto; Machida, Toyohei; Minami, Takeshi (Nuklearmedizin - NuclearMedicine, 1972)
An attempt has been made to produce a new renal scanning agent with faster excretion rate, smaller radiation exposure and cheaper cost than those of chlormerodrin. A new compound l-(4-iodophenyl)-3-[3-(chloromercuri)-2-methoxypropyljurea (abbrev.: IPCM) labeled with 125I was prepared for the first time in four steps with 4-iodoaniline labeled with 125I as the starting material.The kidney affinity of the compound was examined by using male Wistar rats. The distribution of 125I in the organs at various intervals after administration was calculated using an organ/muscle activity ratio. The kidney accumulated more 125I than any other organ.The liver accumulated less 125I than the kidneys, but much more than any other organ. When the body retention of 203Hg-chlormerodrin and 203Hg- or l31I-IPCM was compared, similar biphasic excretion curves were found with both compounds.The urinary and fecal excretion rates of IPCM were nearly the same. Imaging of rabbit kidneys was also tried with a scintillation camera and 131I-IPCM. Some problems of the clinical application of IPCM are discussed with a view to the use of 123I in the future.